HUBUNGAN PENGETAHUAN, DUKUNGAN KELUARGA SERTA PERILAKU PENDERITA DIABETES MELITUS TIPE 2 TERHADAP KEJADIAN ULKUS KAKI DIABETES (Studi di Wilayah Kerja Puskesmas Ngesrep Semarang) - Yunita Amilia; Lintang Dian Saraswati; Muflihatul Muniroh; Ari Udiyono (Jurnal Kesehatan Masyarakat (Undip), 2018)
The occurence of type 2 diabetes mellitus is one type of disease that continues to increase the number of sufferers. One of the most feared DM complications is diabetic foot ulcers. Diabetic foot ulcers are more common in people with type 2 diabetes mellitus. Diabetic foot ulcers can affect mental and physical health, but it also affects the quality of life. The purpose of this study was to determine the correlation between knowledge, family support and the behavior of diabetic mellitus patients type 2 diabetes against occurence of diabetic foot ulcers. This research uses tye analytic observation research type with cross-sectional study design with qualitative data analysis using Chi-Square test and simple random sampling method. The number of male and female respondents are 80 with aged 38-81 years who meet the entry criteria as research subjects. . Based on the result of bivariate analysis with chi-square test proved the relation between BMI (body mass index) (p = 0,02, POR = 0,235; 95% CI 0,074-0,741), behavior (p = 0,002; POR = 6,943; 95% CI 2,099-22,964), family support (p = 0.012; POR = 4,592; 95% CI 1,451-14,529); and knowledge (p = 0,004; POR = 6,111; 95% CI 1,828-20,434) with diabetic foot ulcers. While between age, sex, type of work, education level, family DM history, long suffering from DM, and smoking status is not related with the occurrence of diabetic foot ulcers. From this research can be concluded that the factors that influence the occurrence of diabetic foot ulcers are BMI (body mass index), behavior, family support and knowledge.